Development of continous fibre liquid deposition modelling system - Ong, Effy Wen Wen (Nanyang Technological University, 2023)
Carbon fibre (CF) and carbon fibre reinforced polymer (CFRP) components are valued for their exceptional properties with applications across various industries. The growing demand for CFRP, driven by factors like sustainability and environmental regulations, is expected to result in a 6.5% compound annual growth rate. Despite its popularity, CFRP remains limited to high-performance applications due to complexity, cost, and low production volumes restricted by its primary choice of conventional production methods.